Association between folate and glutamine metabolism and prognosis of kidney cancer - Qin, Jiaxuan; Ouyang, Chaoyue; Zhuang, Xuan (Frontiers in Nutrition, 2025)
BackgroundRecent studies have shown that folate metabolism might influence cancer progression by regulating mitochondrial metabolism and glutamine is involved in the development and progression of several malignancies. This study aimed to explore the association between folate and glutamine metabolism and prognosis of kidney cancer.MethodsWe performed expression analysis, survival analysis, genetic alteration analysis, and tumor immune infiltrate analysis of related genes using platforms such as UALCAN, GEPIA, GEPIA2, cBioPortal, and TIMER. Serum folate, vitamin B12, and methylmalonic acid levels and clinical information of participants in the United States diagnosed with kidney cancer was obtained from the National Health and Nutrition Examination Survey (NHANES) and analyzed using software R.ResultsWe observed that RNA expression levels of certain folate and glutamine metabolism-related genes, particularly MTHFD2 and SLC1A5, were associated with the prognosis of kidney renal clear cell carcinoma (KIRC). Expression differences in these genes were notable between high-stage and low-stage and N1 vs. N0 lymph node metastasis status in KIRC. There was a positive association between glutamine metabolism-related genes and folate metabolism-related genes in KIRC. SLC1A5 was positively correlated with MTHFD2 in KIRC. Folate and glutamine metabolism might play a synchronous role in KIRC prognosis. Strong correlations between MTHFD2 and SLC1A5 expression with KIRC immune infiltrates were found. Higher levels of serum folate may be related to improved cancer-specific survival (CSS) in kidney cancer patients in the U.S.ConclusionFolate and glutamine metabolism-related genes, especially SLC1A5 and MTHFD2, were associated with the prognosis, tumor stage, and lymph node metastasis status in KIRC. Higher KIRC SLC1A5 or MTHFD2 expression levels were associated with higher tumor stages, increased lymph node metastasis possibilities, poorer OS, and poorer RFS. Elevated levels of serum folate may be associated with improved CSS in kidney cancer patients in the United States.